The Role of Csf1 During Preimplantation Mouse Development - Jakešová, Marie (Jihočeská univerzita, 2014)
The aim of this thesis was to investigate the potential role of one candidate cell fate decision influencing gene, colony stimulating factor 1 (Csf1), on the mouse preimplantation development.
The Role of Csf1 During Preimplantation Mouse Development